2023
DOI: 10.20517/cdr.2022.107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in cancer stem cell resistance in head and neck squamous cell carcinoma

Abstract: Despite scientific advances in the Oncology field, cancer remains a leading cause of death worldwide. Molecular and cellular heterogeneity of head and neck squamous cell carcinoma (HNSCC) is a significant contributor to the unpredictability of the clinical response and failure in cancer treatment. Cancer stem cells (CSCs) are recognized as a subpopulation of tumor cells that can drive and maintain tumorigenesis and metastasis, leading to poor prognosis in different types of cancer. CSCs exhibit a high level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Even though not uncontroversially, cancer stem cells are considered as the source of cancer cell renewal and therapy resistance [24,87]. Some studies have therefore attempted to investigate HNSCC stem cells through single-cell transcriptomics.…”
Section: Non-malignant Cells Formed Eight Clusters Comprising T-cells...mentioning
confidence: 99%
“…Even though not uncontroversially, cancer stem cells are considered as the source of cancer cell renewal and therapy resistance [24,87]. Some studies have therefore attempted to investigate HNSCC stem cells through single-cell transcriptomics.…”
Section: Non-malignant Cells Formed Eight Clusters Comprising T-cells...mentioning
confidence: 99%
“…The authors found that GLI mediates the expression of MGMT, which promotes resistance to TMZ [ 139 ]. There are results presenting that the HIF-1α/SHH/GLI1 axis is involved in the resistance of HNSCC to therapy and that HIF-1α reduces the response of HNSCC to radiotherapy [ 78 , 111 , 122 , 145 ]. There are several pieces of evidence documenting the association between CSCs and their signaling pathways and resistance to chemotherapy [ 109 , 113 , 145 ].…”
Section: The Role Of Hh Signaling In Hnscc Tumorigenesismentioning
confidence: 99%
“…There are results presenting that the HIF-1α/SHH/GLI1 axis is involved in the resistance of HNSCC to therapy and that HIF-1α reduces the response of HNSCC to radiotherapy [ 78 , 111 , 122 , 145 ]. There are several pieces of evidence documenting the association between CSCs and their signaling pathways and resistance to chemotherapy [ 109 , 113 , 145 ]. Head and neck CSCs are able to avoid response to therapy due to their overexpression of ABC drug transporters and activation of several pathways [ 146 ].…”
Section: The Role Of Hh Signaling In Hnscc Tumorigenesismentioning
confidence: 99%
“…However, if the formation of distant metastasis occurs, it is also associated with a very poor prognosis [10][11][12]. Several pathways have been suggested to be involved in acquired and intrinsic resistance development, dissemination, and recurrence of HNSCC and have been recently reviewed in [2,13,14]. Here, we highlight the current knowledge of the process of epithelial-mesenchymal transition (EMT) in HNSCC.…”
Section: Introductionmentioning
confidence: 99%